2017
DOI: 10.1038/s41598-017-16230-7
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of OsGRXS17 in rice improves drought stress tolerance by modulating ROS accumulation and stomatal closure

Abstract: Glutaredoxins (GRXs) modulate redox-dependent signaling pathways and have emerged as key mediators in plant responses to environmental stimuli. Here we report that RNAi-mediated suppression of Oryza sativa GRXS17 (OsGRXS17) improved drought tolerance in rice. Gene expression studies showed that OsGRXS17 was present throughout the plant and that transcript abundance increased in response to drought stress and abscisic acid (ABA) treatment. Localization studies, utilizing GFP-OsGRXS17 fusion proteins, indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 66 publications
2
43
0
Order By: Relevance
“…GRXS17 was previously proposed to improve thermo-, drought- and oxidative-tolerance by enhancing ROS scavenging capacities and expression of Heat-Shock Proteins. This might occur by modulation of gene expression, enzyme activity or protection of antioxidant enzymes (Wu et al, 2012, 2017; Hu et al, 2017). Our data suggest an additional function of GRXS17 through its chaperone activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRXS17 was previously proposed to improve thermo-, drought- and oxidative-tolerance by enhancing ROS scavenging capacities and expression of Heat-Shock Proteins. This might occur by modulation of gene expression, enzyme activity or protection of antioxidant enzymes (Wu et al, 2012, 2017; Hu et al, 2017). Our data suggest an additional function of GRXS17 through its chaperone activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, for most of its partners, the role of the Fe-S cluster remained enigmatic. Genetic evidence from different plant species suggests a protective role of GRXS17 during thermal, genotoxic and drought stress (Cheng et al, 2011; Wu et al, 2012; Wu et al, 2017; Iñigo et al, 2016; Hu et al, 2017), in meristem development (Knuesting et al, 2015), hormonal responses (Cheng et al, 2011), and during redox-dependent processes (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the possible genetic basis of the observed increased susceptibility in the high nitrogen environment, the 126 genes annotated at NIS3 were investigated (Additional le 15). We considered as good candidates genes either involved in biotic stress response (twenty-nine pathogenesisrelated genes), abiotic stress response (OsTIP3;1, [64] and RIPER6 [65]), the regulation of both stresses (OsGRXS17, [66] and OsTPR1 [67]), or nitrogen metabolism (OsPORB, [68] and a polylpolyglutamate synthetase [69]). The possible modulation of the M. oryzae pathogenicity program in response to a high nitrogen environment was also a hypothesis based on our previous results [26].…”
Section: Nis3 a Qtl Conferring Partial Resistance Strongly Impacted mentioning
confidence: 99%
“…Phenotyping of IR64-derived near-isogenic lines (NILs) with varying leaf size showed that plants with broad leaves performed better than those with short and narrow leaves (Farooq et al, 2010). Change in leaf size, together with stomatal opening and closure can be an adaptive mechanism for plants to minimize water loss (Farooq et al, 2010, Hu et al, 2017. Leaf size is an important agronomic trait in rice and was shown to moderately correlate to panicle numbers (Rabara et al, 2014a).…”
Section: Drought and High Temperature Stress Effects And Response Mecmentioning
confidence: 99%